I CONTROL MY OWN ENGLISH LEARNING: DEVELOPING SELF-REGULATION IN ELEMENTARY ELL USING SELF-ASSESSMENT AND EXPLICIT STRATEGY INSTRUCTION - Azatova, Samantha (TEFLIN Journal, 2021)
This study examined the effectiveness of using self-assessment and explicit strategy instruction to develop self-regulation in 4 th grade lower-intermediate English Language Learners (ELLs) in an English-medium international school. The study took place in the English as an Additional Language (EAL) Department of the school, which is a student support department that works with students to develop English proficiency in order for them to participate in an English-medium school. In comparison with other levels of ELLs, it was found that intermediate students at the 4 th grade were the least able to make gains in English language development due to overconfidence in their current language proficiency. To overcome this, they were taught to use a selfregulatory cycle in conjunction with self-assessment and explicit strategy instruction. After four months, the students were consistently able to set goals using elements of the self-assessment tool they were taught and the strategies they learned, monitor their progress, and then reflect on their growth as English language learners. These findings are discussed in terms of their relevance to student growth as autonomous, engaged English learners.